Description of Sedentary Behavior and Nutritional Status in Adolescents at SMAN 4 Kota Kediri - Nuuri Hisyam; Ardhi Mardiyanto Indra Purnomo; M. Akbar Husein (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2023)
This study aims to evaluate nutritional status and sedentary behavior in adolescents in Indonesia. Adolescence is a phase of growth and development that requires good nutrition. However, adolescents are faced with the risk of malnutrition or overnutrition, as well as micronutrient deficiency. In addition, the development of science and technology has a significant impact on adolescent behavior, with the use of sophisticated and instantaneous equipment that contributes to sedentary behavior. Lack of knowledge about nutritional value can also negatively impact adolescent health. Therefore, it is important to understand the sedentary behavior and nutritional status conditions of adolescents in this modern era. This  study used descriptive quantitative methods with a population of 450 adolescents and a sample of 115 students. Data analysis was performed using Excel. The results showed that most adolescents in SMAN 4 Kediri City experienced sedentary behavior, with 103 adolescents (90%). And the measurement results showed that most adolescents had normal nutritional status, with 75 adolescents (66%) having an average body mass index (BMI) of 20.9